Job Titles Matching Using Bayesian Network - Abu Bakar, Azuraini (2011)
This study proposed a solution to assist employers during job advertisement phase by identifying suitable soft skills with its relevancy to the job title. The proposed solution called Soft Skills Advisory System (SSAS) was developed which consists of the User Interface and the Decision Making components.